Citizen and state in the philosophy of Spinoza - LeBuffe , Michael (Interstices: Journal of Architecture and Related Arts, 2021)
In Spinoza's view, the highest purpose of society is to make each human being in it as well off as possible. He takes wellbeing to consist in knowledge, and the freedom from irrational, highly passionate ideas. On Spinoza's conception of religion, many citizens in any given society are motivated primarily by highly irrational, highly passionate religious ideas. Here I argue that Spinoza's psychology suggests that there are two possible ways to overcome such ideas. Society might work to eliminate religious ideas in citizens, thereby relieving them of their most irrational and harmful beliefs; or society might work to give citizens different, highly rational beliefs while leaving religion untouched. I argue that, given Spinoza's other commitments, only the second method could work.